2016
DOI: 10.1111/adj.12385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium phosphate addition to fluoride containing dental varnishes on enamel demineralization

Abstract: MI Varnish containing fluoride and CPP-ACP was superior to the other varnishes in protecting against enamel demineralization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
65
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 29 publications
10
65
1
3
Order By: Relevance
“…On the other hand, some studies claim that the addition of Ca and P ions to a glass ionomer-based material increases their availability for binding to the released F ions. 21,22 This is in accordance with the concept that a high initial concentration of F is better for inhibiting the formation of new lesions, while lower initial concentration is most effective for remineralization and control of the progression of lesions. 23 In addition, we hypothesize that a resinmodified glass-ionomer with Ca used as coating material could be effective in the long term since it acts mainly in the subsurface of the lesion in adjacent area of the material as showed by CSH values ( Figure 4A), but further studies are needed to elucidate this.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, some studies claim that the addition of Ca and P ions to a glass ionomer-based material increases their availability for binding to the released F ions. 21,22 This is in accordance with the concept that a high initial concentration of F is better for inhibiting the formation of new lesions, while lower initial concentration is most effective for remineralization and control of the progression of lesions. 23 In addition, we hypothesize that a resinmodified glass-ionomer with Ca used as coating material could be effective in the long term since it acts mainly in the subsurface of the lesion in adjacent area of the material as showed by CSH values ( Figure 4A), but further studies are needed to elucidate this.…”
Section: Discussionsupporting
confidence: 87%
“…While some authors have observed that after 24 hours Profluorid has released approximately 17% of its fluoride content (201.34 μmol/g) and Clinpro White Varnish has released 16% (175 .87 μmol/g) [27], others have found that after 24 hours the percentage of fluoride released by Clinpro White Varnish was 6% and 20% after 7 days [28]. Bolis et al .…”
Section: Discussionmentioning
confidence: 99%
“…Studies are in progress to give an idea about the effects of these materials with derivatives of calcium phosphate on carious enamel lesions. A good results were concluded about the ability of these materials to protect enamel against the demineralization [22] .…”
Section: Fig (1)mentioning
confidence: 99%